2005
DOI: 10.1007/s10729-005-5217-2
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Detecting Runs of Good and Bad Clinical Outcomes on Variable Life-Adjusted Display (VLAD) Charts

Abstract: In recent years there has been a growing need for effective monitoring of clinical outcomes. Two techniques for continuous monitoring that have emerged almost simultaneously are the Variable Life-Adjusted Display (VLAD) and risk-adjusted cumulative sum charts (CUSUM). The VLAD provides clinicians and management with an easily understandable overview of outcome history and is now in routine use in several hospitals. Although it can indicate runs of good and bad outcomes, unlike the CUSUM, it does not provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…A signaling rule provides an objective and quantitative way for assessing the plotted points and determining appropriate times for taking action. Sherlaw-Johnson (2005) mapped the control limits of the risk-adjusted cumulative sum (CUSUM) chart onto the variable life-adjusted display but the resulting signaling rule is complicated because the control limits change with inclusion of data from every new surgical operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A signaling rule provides an objective and quantitative way for assessing the plotted points and determining appropriate times for taking action. Sherlaw-Johnson (2005) mapped the control limits of the risk-adjusted cumulative sum (CUSUM) chart onto the variable life-adjusted display but the resulting signaling rule is complicated because the control limits change with inclusion of data from every new surgical operation.…”
Section: Introductionmentioning
confidence: 99%
“…Their approach uses a risk-adjusted likelihood ratio statistic as the penalty-reward score. The riskadjusted CUSUM chart and variable life-adjusted display are developed using two different approaches and are viewed as two different charts (Spiegelhalter et al 2003;Rogers et al 2004;Sherlaw-Johnson 2005;Woodall 2006). Gan, Lin, and Loke (2012) showed that the risk-adjusted CUSUM chart (Steiner, Cook, and Farewell 1999) and the CUSUM chart constructed using the likelihood ratio statistic based on the variable lifeadjusted display's monitoring statistic (difference between expected and actual mortality) are in fact the same because the two monitoring statistics contain the same information.…”
Section: Introductionmentioning
confidence: 99%
“…It has been pointed out that the CUSUM chart is not, by itself, very revealing and a combined chart has been proposed [18]. We have adopted this approach of combining the two charts but in a slightly simpler manner; CUSUM signals are indicated by the presence of a prominent arrow.…”
Section: Discussionmentioning
confidence: 99%
“…A solution to this problem is a surveillance scheme that combines the VLAD and RA-CUSUM 6. The VLAD plot indicates the trends, and the RA-CUSUM2 signals that the trends are potentially important.…”
mentioning
confidence: 99%